Integration Of Glutaraldehyde Onto Immuno-Membrane For Polyaniline-Based Electrochemical Biosensor - Shaimi, Roswani (2013)
Development of membrane for bio-sensing applications for epidemics control has a huge global impact especially for public health. This research explored the electrochemical biosensor with polyaniline (PANI) as a transducer through analyzing the biotin-bovine serum albumin (BSA) interaction as a model system. As membrane appeared as the platform for protein immobilization, selection of suitable membrane is required to create a sensitive and specific biosensor. In measurement of membrane performance, membrane protein binding abilities were quantitatively determined. Among the tested membranes, NC-180 appeared as the most suitable lateral flow membrane as it performed high protein binding ability and short lateral wicking time. To increase the membrane protein binding ability, NC-180 was then subjected to membrane modification using glutaraldehyde (GA) solution. The protein binding of the modified membrane with GA was able to retain up to temperature of 60oC. In the present study, the effect of various integration factors such as the concentration of GA, integration time and number of the integration layer on membrane‟s protein binding ability was investigated. The optimum integration conditions were determined using response surface methodology (RSM).